2000
DOI: 10.1016/s0378-1097(00)00392-x
|View full text |Cite
|
Sign up to set email alerts
|

Antisense expression of the calmodulin gene from Colletotrichum trifolii impairs prepenetration development

Abstract: Calmodulin is a ubiquitous highly conserved calcium binding protein involved in cell signalling. Previous studies in our laboratory suggested a role for calmodulin in prepenetration morphogenesis in Colletotrichum trifolii, the causal agent of alfalfa anthracnose. In this report, we describe the cloning, sequencing and partial characterization of the calmodulin gene from C. trifolii. The gene is present as a single copy in the genome of C. trifolii and its predicted amino acid sequence shows considerable homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…These protein complexes then bind to calcineurin A, a highly conserved protein phosphatase (Luan, 2009). In phytopathogenic fungi, CaMs and CNBs have been involved in virulence (Lee and Lee, 1998;Warwar et al, 2000;Uhm et al, 2003;Harel et al, 2006;Ahn and Suh, 2007;Egan et al, 2009;Cervantes-Chávez et al, 2011), and comparative genomics of the Ca 2+ /CaM/CNB pathway suggest that it is highly conserved in fungi (Rispail et al, 2009).…”
Section: Specificity Of Mutually Activated Mapk Pathwaysmentioning
confidence: 99%
“…These protein complexes then bind to calcineurin A, a highly conserved protein phosphatase (Luan, 2009). In phytopathogenic fungi, CaMs and CNBs have been involved in virulence (Lee and Lee, 1998;Warwar et al, 2000;Uhm et al, 2003;Harel et al, 2006;Ahn and Suh, 2007;Egan et al, 2009;Cervantes-Chávez et al, 2011), and comparative genomics of the Ca 2+ /CaM/CNB pathway suggest that it is highly conserved in fungi (Rispail et al, 2009).…”
Section: Specificity Of Mutually Activated Mapk Pathwaysmentioning
confidence: 99%
“…Spore germination is a key step in the colonization process of a new environment by filamentous fungi. Recent studies of C. trifolii have revealed that various signaling molecules, including calcium, cyclic AMP (cAMP), calmodulin, and protein kinases, are important players in regulating spore germination (14,46,50). Here we described the involvement of the small GTPase Cdc42 in this process; it will be of interest to examine the relationship between Cdc42 and these other signaling components.…”
mentioning
confidence: 90%
“…Previous studies of C. trifolii have shown that an increase in endogenous cAMP levels by using cAMP-elevating agents, such as 8-Br-cAMP, sodium fluoride, and 3-isobutyl-1-methylxanthine, also results in induction of appressorial differentiation on a noninductive surface, suggesting a possible linkage between CtCdc42 and the cAMP signaling pathway (50). Moreover, several signaling molecules in C. trifolii that are important for appressorium development have been isolated and characterized, including the catalytic subunit of PKA, calmodulin, and lipid-induced protein kinase (14,46,49,50). Molecular analysis of the connection of CtCdc42 with these molecules will improve the understanding of signaling pathways involved in appressorium development in C. trifolii.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, genetic transformation is a powerful instrument to study the pathogenicity mechanisms of this fungus at the molecular level. Transformation is widely employed in genetic studies in fungi and has been used in gene disruption (Cummings et al, 1999;Fujimoto et al, 2002;Jin et al, 2005;Seong et al, 2005), gene replacement (Oeser et al, 2002) and gene silencing (Warwar et al, 2000). Mutants have been demonstrated to be a valuable resource for genetic and molecular analysis.…”
Section: Introductionmentioning
confidence: 99%